Review: Taxonomic Contribution For Ecotourism Development In Indonesia - Chairiyah, Nurul (Journal of Indonesian Tourism and Development Studies, 2013)
This paper describes about the role of taxonomic in ecotourism development in Indonesia. Development and management of ecotourism in Indonesia recently are still quite slow and inadequate. It is due to the lack of knowledge of local community about the information of flora and fauna which is used as ecotourism attraction. Therefore the taxonomical science needs to be applied to the development of ecotourism in Indonesia. In addition, some species which are used as tourist attractions needs to be identified and classified to preserve the resource. Implementation of taxonomy related to survey, documentation, data collection, identification and classification to establish the identity of a species for ecotourism attraction. Methods are commonly used for the implementation of taxonomy in the ecotourism development, i.e. (1) morphological observation, (2) vocalizations and (3) molecular analysis. Morphological observations can be applied by qualitative and quantitative observations. Qualitative observation is an observation of a species, which is related to morphology and coloration, and comparison with other species which are suspected related. Quantitative observation is a morphometric analysis, which is a concept of quantitative analysis of the species that related to the size and shape of a species. Vocalization method is applied by determining the vocal character of a species, by comparing the data, which has obtained, with the data vocals from other species which are suspected related. Molecular analysis is commonly used to support the identification of morphological and vocalization of the species. Molecular methods, which are commonly applied for species identification, are usually hybridization, DNA sequencing, restriction mapping, chromosome banding and immunological method Keywords: taxonomy, ecotourism, Indonesia, morphological observation, vocalization, molecular identification